2021
DOI: 10.1556/1647.2021.00055
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in the intensive care unit: an essential tool for diagnosis, monitoring and guiding clinical decision-making

Abstract: In the last years, new trends on patient diagnosis for admission in cardiac intensive care unit (CICU) have been observed, shifting from acute myocardial infarction or acute heart failure to non-cardiac diseases such as sepsis, acute respiratory failure or acute kidney injury. Moreover, thanks to the advances in scientific knowledge and higher availability, there has been increasing use of positive pressure mechanical ventilation which has its implications on the heart. Therefore, there is a growing need for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…ICU is a place where modern medical theory and high-tech modern equipment were applied to conduct specialized and centralized monitoring, treatment, and nursing for critically ill patients [ 34 ]. Most of the patients in the ICU are in serious disease conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU is a place where modern medical theory and high-tech modern equipment were applied to conduct specialized and centralized monitoring, treatment, and nursing for critically ill patients [ 34 ]. Most of the patients in the ICU are in serious disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our pooled results showed that CRRT showed similar efcacy in improving renal function and short-term mortality in patients with renal failure, further confrming the important role of CRRT in the treatment of renal impairment. ICU is a place where modern medical theory and high-tech modern equipment were applied to conduct specialized and centralized monitoring, treatment, and nursing for critically ill patients [34]. Most of the patients in the ICU are in serious disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, perfusion can be evaluated through LV Ejection Fraction (EF), but it is well known that this parameter is greatly influenced by LV geometry, heart rate and loading conditions (preload and afterload). As a result of that, its usefulness is limited in critically ill patients [2]. Hence, in severe shock states, the estimation of CO, measured as a calculation of stroke volume (SV) times the heart rate, is a more reliable quantitative parameter as it truly reflects circulatory status and organ perfusion [9].…”
Section: Echocardiographic Variablesmentioning
confidence: 99%
“…Normal LVOT VTI is higher than 18 cm and it could be used as a surrogate for SV, which is also an important predictor of fluid responsiveness. In particular, there are static measures of fluid responsiveness (inferior vena cava (IVC) diameter, CI and left ventricular enddiastolic area (LVEDA)) and dynamic measures (IVC distensibility in spontaneous breath and LVOT VTI respiratory variability) [2,7,10].…”
Section: Echocardiographic Variablesmentioning
confidence: 99%
See 1 more Smart Citation